Searching for the link; mechanisms underlying liver regeneration and recurrence of colorectal liver metastasis post partial hepatectomy. Issue 8 (28th March 2019) - Riddiough, Georgina E.; Fifis, Theodora; Muralidharan, Vijayaragavan; Perini, Marcos V.; Christophi, Christopher
Abstract: Despite excellent treatment of primary colorectal cancer, the majority of deaths occur as a result of metastasis to the liver. Recent population studies have estimated that one quarter of patients with colorectal cancer will incur synchronous or metachronous colorectal liver metastasis. However, only one quarter of these patients will be eligible for potentially curative resection. Tumor recurrence occurs in reportedly 60% of patients undergoing hepatic resection, and the majority of intrahepatic recurrence occurs within the first 6 months of surgery. The livers innate ability to restore its homeostatic size, and volume facilitates major hepatic resection that currently offers the only chance of cure to patients with extensive hepatic metastases. Experimental and clinical evidence supports the notion that following partial hepatectomy, liver regeneration (LR) paradoxically drives tumor progression and increases the risk of recurrence. It is becoming increasingly clear that the processes that drive liver organogenesis, regeneration, and tumor progression are inextricably linked. This presents a major hurdle in the management of colorectal liver metastasis and other hepatic malignancies because therapies that reduce the risk of recurrence without hampering LR are sought. The processes and pathways underlying these phenomena are multiple, complex, and cross‐communicate. In this review, we will summarize the common mechanisms contributing to both LR and tumor recurrence.